Micro-extração em fase sólida (SPME) in situ e comparação de compostos voláteis em variedades de manga (Mangifera indica L.) resistentes e suscetíveis à mosca-das-frutas Anastrepha obliqua (Macquart) (Diptera: Tephritidae) - Tosta, Christiann Davis [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Many commercial varieties of mango (Mangifera indica L.) are susceptible to pests called fruit flies, as Anastrepha obliqua, an important specie. This leads to the need of the use of chemical pesticides, burdening the production and generating environmental problems. Some mango varieties are resistant to fruit flies and therefore having factors that differentiate it when comparing to the susceptible. The objective of this study was to perform exploration of compounds and to identify factors of resistance and/or attraction. Peel characteristics were analyzed and volatile compounds obtained by solid phase micro extraction (SPME) in situ were identified and compared in the latex (sap) and fruits from resistant and susceptible varieties. This technique is useful to reveal the compounds really liberated on orchard, avoiding artefacts formation and the losing of compounds. Electroantenongraphic and wind tunnel attraction tests were performed using the proportion of the major compounds emitted by mango fruits. The results showed higher density of lactiferous ducts in the resistant variety and differences of latex and fruit volatile compounds profiles, as well as in different stages of ripening. Green fruits showed no esters, which became part of the main compounds in the total ripe stage, mainly ethyl octanoate and methyl octanoate. The α-copaene, α-gurjunene and β-selinene compounds seem possible role in repellency in unripe fruits, including possibly functioning as green stage markers, since their levels fall with maturation while its esters have increased. The compounds found in greater quantity in the condition of resistance were limonene, a- pinene, myrcene and humulene, while the condition of susceptibility were marked by ethyl octanoate, methyl octanoate, δ-3-carene and aloaromadendreno. The synthetic blend based on nine main compounds of the variety 'Palmer' proved attractive to Anastrepha...

As variedades de manga (Mangifera indica L.) mais produzidas comercialmente são suscetíveis às pragas comumente denominadas moscas-dasfrutas, principalmente a espécie Anastrepha obliqua, o que leva a necessidade de emprego de defensivos químicos, onerando a produção e gerando problemas ambientais com resíduos químicos. Algumas variedades de manga são totalmente resistentes às moscas-das-frutas e, portanto, possuem fatores que a diferenciam das suscetíveis. O objetivo deste trabalho foi executar prospecção de compostos e características na busca da identificação dos referidos fatores químicos e/ou físicoquímicos de resistência e/ou atração. Para tanto foram analisadas características de cascas, látex e comparados os compostos identificados e obtidos por micro-extração em fase sólida (SPME) in situ em frutos de variedades resistentes e suscetíveis. Identificados os compostos voláteis, realizaram-se testes eletroantenográficos e testes de atração em túnel de vento com blends sintéticos baseados na proporção dos principais compostos emitidos pelos frutos. Os resultados revelaram maior densidade de dutos lactíferos em variedade resistente e diferenças nos perfis de compostos voláteis de látex e de frutos, assim como nos diferentes estágios de maturação. Frutos verdes não apresentaram ésteres, que por sua vez passaram a integrar os principais compostos na fase madura, principalmente octanoato de etila e octanoato de metila. Os principais compostos encontrados em maior quantidade na condição de resistência foram limoneno, a-pineno, mirceno e humuleno, enquanto os que marcaram a condição de suscetibilidade foram octanoato de etila, octanoato de metila, δ-3-careno e aloaromadendreno. Os compostos α-copaeno, α-gurjuneno e β-selineno aparentam possível papel na repelência nos frutos ainda verdes, inclusive possivelmente funcionando como marcadores deste estágio...
Keywords: Ecologia quimica; Compostos orgânicos voláteis; Manga (Fruta); Mosca; Anastrepha; Fly